The United Nations - Ross, Stewart (Sussex : Hodder Wayland, 2004)
Discusses the establishment of the United Nations, its function in preventing war and eliminating poverty, and its role in various international conflicts.
Keywords: United Nations -- History -- Juvenile literature; United Nations -- History; United Nations -- History